Autologous Breast Reconstruction Skin Paddle Designs: Classification and Aesthetic Outcomes - Pestana, Ivo A.; Walker, Nicholas J. (Journal of Reconstructive Microsurgery Open, 2019)
Objective Present study was conducted to identify common mastectomy patterns and autologous skin paddle designs, to identify patient characteristics that influence these patterns, and assess aesthetic outcomes associated with each pattern.Methods Autologous breast reconstructions over 5 years were reviewed. Mastectomy type and resultant skin paddle were categorized into four mastectomy type/skin paddle design groups based on the amount of native “Skin Spared” after mastectomy and the resultant flap skin paddle designed. Groups were designated as skin-sparing mastectomy 1 (SS1)/large elliptical skin paddle, skin-sparing mastectomy 2 (SS2)/small elliptical skin paddle, skin-sparing mastectomy 3 (SS3)/areola skin paddle, and skin-sparing mastectomy 4 (nipple-sparing mastectomy, SS4)/no skin paddle. Surveys were performed to validate the classification system and critique aesthetic outcomes.Results A total of 89 autologous breast reconstructions were included. Radiotherapy was used in 45.6% of SS1 patients versus 29.2% in SS2 and 12.5% in SS3/SS4. Mean body mass index (BMI) was 30 in SS1/SS2 and 26 in SS3/SS4 mastectomy types (p = 0.045). Delayed reconstruction was performed in 96.5% SS1 versus 62.5% in SS2 and only 25% of SS3/SS4 (p < 0.0001). Physicians and Non-MD personnel correctly categorized 85.8 and 76.1% of skin paddle designs, respectively. Over 75% of those surveyed rated the reconstruction aesthetic outcome as “good-excellent” regardless of the pattern group.Conclusions Patients in SS1/SS2 groups had a higher incidence of radiotherapy, delayed reconstruction, and higher BMI compared with the SS3/SS4 groups. The classification system is recognizable and may provide improved patient education and communication between healthcare providers. All mastectomy type/skin paddle designs received high aesthetic ratings.
Keywords: mastectomy; autologous breast reconstruction; free flap; flap inset